UNO’s Sustainable Development Goals in academic courses: a pilot analysis on the programs of an Italian university - Saramin, A.; Del Pin, M.; Miotto, E.; Smaniotto, C.; Cadez, L.; Kodilja, R.; Marangon, F.; Parpinel, M.; Brunelli, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Universities are critical in educating tomorrow’s citizens and achieving the Sustainable Development Goals of the United Nations Organization. The aim of this study was to investigate the integration of these goals in the curricula of an Italian university. Study design. Cross-sectional study. Methods. In February 2021, as part of the annual Syllabus preparation for each course, the teaching staffs at the University of Udine (Italy) were asked to complete an additional section in which they could indicate up to three Sustainable Development Goals for their courses. Descriptive statistics, Chi-square test and logistic regression were performed to determine whether the professors’ sex, age, or department affected the likelihood of mentioning Sustainable Development Goals. Results. In 723 courses, 360/1040 professors 59% male, mean age 53 years (range 30-73), mentioned one (29%), two (23%), or three (31%) Sustainable Development Goals. No Sustainable Development Goals were mentioned in 16% of courses, the majority of which were from the Mathematical, Computer and Physical Sciences Department (58%). The top six Sustainable Development Goals quoted were: Good health and well-being (35%), Responsible consumption and production (22%), Quality education (17%), Industry, innovation and infrastructure (13%), Gender equality (13%), Decent work and economic growth (13%). The least frequently mentioned Goal was Life below water (1%). Women (p<0.0001) and senior professors (p=0.0148) were more likely to consider at least one of the Sustainable Development Goals, while Mathematical, Computer and Physical Sciences Department showed a negative correlation (p<0.0001). Conclusions. Gaps were identified with respect to specific Sustainable Development Goals, but discrepancies between departments may indicate deficits in respondent awareness. A transparent description of the Sustainable Development Goals in courses is recommended, to increase students’ and university’s engagement in sustainability